2019
DOI: 10.1038/s41418-019-0356-z
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 promotes lipophagy and chaperon-mediated autophagy to protect hepatocytes against lipotoxicity

Abstract: Lipophagy is a lysosomal lipolytic pathway that complements the actions of cytosolic neutral lipases. Chaperon-mediated autophagy (CMA) triggers lipid droplets (LDs) breakdown, to initiate lipolysis via either cytosolic lipases or macroautophagy. SIRT3, a mitochondrial NAD + -dependent deacetylase, regulates the acetylation status and activity of many substrates involving in energy metabolism. However, the role of SIRT3 in regulating lipophagy is controversial. The current study showed that SIRT3 expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 68 publications
2
89
0
Order By: Relevance
“…effects of FFAs on autophagic flux using human nontumor hepatic cell line L02 cells (human hepatic L02 cells) and found that autophagic flux was blocked at the late hour (24,36 h) of steatosis due to homeostatic imbalance Kim et al, 2018;Zhang et al, 2019).Likewise, our results were further confirmed in vitro experiments ( Figure 4B). In particular, combined treatment with autophagy inhibitor (3-MA) evidently inhibited Cori-mediated decrease of p62 protein levels ( Figure 4B).…”
Section: Discussionsupporting
confidence: 83%
“…effects of FFAs on autophagic flux using human nontumor hepatic cell line L02 cells (human hepatic L02 cells) and found that autophagic flux was blocked at the late hour (24,36 h) of steatosis due to homeostatic imbalance Kim et al, 2018;Zhang et al, 2019).Likewise, our results were further confirmed in vitro experiments ( Figure 4B). In particular, combined treatment with autophagy inhibitor (3-MA) evidently inhibited Cori-mediated decrease of p62 protein levels ( Figure 4B).…”
Section: Discussionsupporting
confidence: 83%
“…The OCR was determine by using a Seahorse Bioscience XF24-3 Extracellular Flux Analyzer (Agilent, Santa Clara, CA, USA), as described previously [26]. 3T3-L1 cells were seeded in XF24-well microplates (Seahorse Bioscience, Billerica, MA, USA) at 5 × 10 5 cells per well.…”
Section: Seahorse Analysismentioning
confidence: 99%
“…Sirt3 deficiency inhibits macroautophagy and disrupts mitochondrial homeostasis in cardiac aging mice [24,25]. Overexpression of Sirt3 induces macroautophagy and CMA to protect against lipotoxicity in hepatocytes [26]. Sirt3 overexpression activates macroautophagy to prevent mitochondrial injury and cardiomyocyte apoptosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…SIRT3 also acts as a positive regulator of autophagy via its deacetylation of crucial autophagic proteins. [17][18][19] Our previous study revealed that ablation of SIRT3 directly impairs EC-associated autophagy, resulting in severe microvascular rarefaction. Moreover, several groups have found that the loss of SIRT3 causes a shift toward glycolytic metabolism.…”
Section: Introductionmentioning
confidence: 99%